Plant fiber composite eVA foamed material and preparation method

By activating zinc ricinoleate to modify plant fibers, a hydrophobic-hydrophilic transition layer is formed, which solves the problem of poor compatibility between plant fibers and EVA matrix, improves cell uniformity and stability, and enhances the mechanical properties and foaming stability of the material.

CN120818193BActive Publication Date: 2025-11-25SICHUAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511343599.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-19
Publication Date
2025-11-25
Estimated Expiration
2045-09-19

AI Technical Summary

Technical Problem

The poor compatibility between plant fibers and EVA matrix leads to weak interfacial bonding, uneven fiber dispersion, and high moisture absorption, which seriously affects the mechanical properties and foaming stability of the material.

Method used

Plant fibers were modified by activating zinc ricinoleate with trisodium methylglycine diacetate and sodium L-lysine to form a hydrophobic-hydrophilic transition layer, which improved the compatibility and dispersibility of the fibers with EVA. The modified fibers acted as a "skeleton" in the cell wall, stabilizing the cell structure.

Benefits of technology

It significantly improves the uniformity and stability of the foam cells, enhances the mechanical properties and foaming stability of the material, and reduces the moisture absorption rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120818193B_ABST
    Figure CN120818193B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of polymer composite material preparation, and discloses a plant fiber composite EVA foaming material and a preparation method. The plant fiber composite EVA foaming material is prepared from raw materials including modified plant fiber and EVA in a mass ratio of (1:9) to (4:6). The modified plant fiber is obtained by modifying plant fiber after activating zinc ricinoleate with trisodium methyl glycine diacetate and sodium L-lysine. The trisodium methyl glycine diacetate and sodium L-lysine are used to activate zinc ricinoleate for the first time, and then the activated zinc ricinoleate is used to modify plant fiber. The hydrophobicity, dispersibility and compatibility of the plant fiber modified by the trisodium methyl glycine diacetate and the sodium L-lysine are obviously improved. The uniformity of the foaming material prepared by compounding the plant fiber with EVA is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer composite material preparation technology, specifically to plant fiber composite EVA foam material and its preparation method. Background Technology

[0002] Plant fiber composite EVA foam materials have attracted much attention in footwear, packaging, and building materials due to their lightweight, environmentally friendly, and biodegradable properties. However, the surface of plant fibers is rich in hydrophilic hydroxyl groups, which have poor compatibility with the hydrophobic EVA matrix, resulting in weak interfacial bonding, uneven fiber dispersion, and high moisture absorption, which seriously restricts the material's mechanical properties and foaming stability.

[0003] Currently, there are three main methods for improving fiber-matrix compatibility, but limitations still exist: 1) Coupling agent treatment (such as silanes and titanates): Coupling agent residues may hinder material biodegradation, and the interface layer is prone to aging and peeling after long-term use. 2) Graft copolymerization modification: The process is complex, requiring precise control of the grafting rate to avoid fiber embrittlement, and industrial production costs are high. 3) Addition of solubilizers: Excessive addition leads to a decrease in EVA crosslinking degree and insufficient cell wall strength during foaming. Especially in the foaming process, the above methods still face common problems: insufficient cell wall strength caused by poor bonding between the fiber and melt interface significantly increases the risk of cell merging or rupture during gas expansion; at the same time, the lack of a cell structure stabilization mechanism further causes key problems such as uneven density distribution and decreased resilience in the product.

[0004] In view of this, the present invention is proposed. Summary of the Invention

[0005] The present invention aims to solve at least one of the above technical problems and provides a plant fiber composite EVA foam material and a preparation method thereof. The foam material provided by the present invention has a high density, fine and uniform, and stable cell structure.

[0006] To achieve the above objectives, the first technical solution adopted by the present invention is as follows:

[0007] Plant fiber composite EVA foam material, the raw materials contain modified plant fiber and EVA in a mass ratio of (1:9)-(4:6);

[0008] The modified plant fiber is obtained by modifying plant fiber by activating zinc ricinoleate with trisodium methylglycine diacetate and sodium L-lysine.

[0009] Preferably, the mass ratio of trisodium methylglycine diacetate, sodium L-lysine, and zinc ricinoleate is 1: (1.8-3.5): (1.6-4.2).

[0010] Preferably, the plant fiber comprises any one of seed or hair fiber, bast fiber, leaf vein fiber, fruit fiber, grass / poaceae fiber.

[0011] Preferably, the plant fiber comprises any one of bamboo fiber, ramie fiber, straw fiber, cotton fiber, kapok fiber, flax fiber, jute fiber, kenaf fiber, hemp fiber, sisal fiber, abaca fiber, coconut shell fiber, sugarcane residue fiber, reed fiber, miscanthus fiber.

[0012] Preferably, before the modification of the plant fiber, at least one pretreatment of washing, drying, and swelling treatment is further included.

[0013] Preferably, the method for modifying the plant fiber comprises: vacuum-impregnating the plant fiber in the activated zinc ricinoleate solution until the chelation reaction is completed, and then drying.

[0014] Preferably, after the drying, the plant fiber with the completed chelation reaction can be again impregnated in the activated zinc ricinoleate solution for 30-60 min, and then dried again.

[0015] Preferably, the solid-liquid ratio of the plant fiber to the activated zinc ricinoleate solution is 1:(8-25) g / g.

[0016] The second technical solution adopted by the present application is:

[0017] The preparation method of the plant fiber composite EVA foaming material comprises:

[0018] After the modified plant fiber is mixed with EVA, the mixture is mixed at 90-110 ℃ for 15-30 min, and then foamed at 180-190 ℃ and 8-15 Mpa for 8-15 min.

[0019] Preferably, an auxiliary agent is further added in the mixing process.

[0020] Compared with the prior art, the present application has the following beneficial effects:

[0021] For the first time, the present application activates zinc ricinoleate by using methyl glycine diacetate trisodium and L-lysine sodium, and then modifies the plant fiber by using the activated zinc ricinoleate. The hydrophobicity, dispersibility, and compatibility of the modified plant fiber are obviously improved. The uniformity of the foaming material prepared by blending the modified plant fiber with EVA can be significantly improved. BRIEF DESCRIPTION OF DRAWINGS

[0022] Figure 1 The results of the hydrophobicity and hydrophilicity demonstration and test of the modified bamboo fiber in Example 1;

[0023] Figure 2 The results of the hydrophobicity and hydrophilicity demonstration and test of the unmodified bamboo fiber in Comparative Example 1;

[0024] Figure 3 Fig. 2 shows the SEM images of the foamed materials prepared in Example 1, Comparative Example 2 and Comparative Example 3, wherein a, b and c are the SEM images of the foamed materials prepared in Example 1, Comparative Example 2 and Comparative Example 3, respectively.

[0025] Figure 4 Fig. 3 shows the cross-sectional cell images of the foamed materials prepared in Example 1, Comparative Example 2 and Comparative Example 3, wherein a, b and c are the cross-sectional cell images of the foamed materials prepared in Example 1, Comparative Example 2 and Comparative Example 3, respectively.

[0026] Figure 5 Fig. 4 shows the SEM images of the foamed materials prepared in Comparative Example 3, Comparative Example 4 and Comparative Example 5, wherein a, b and c are the SEM images of the foamed materials prepared in Comparative Example 3, Comparative Example 4 and Comparative Example 5, respectively. DETAILED DESCRIPTION

[0027] In order to make the objects, technical solutions and advantages of the present application clearer, the present application will be further described in detail below with specific embodiments. It should be understood that these descriptions are only exemplary and are not intended to limit the scope of the present application. Moreover, in the following description, the description of well-known structures and techniques is omitted to avoid unnecessary confusion of the concept of the present application. The specific conditions not mentioned in the examples are carried out according to the conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments not mentioned by the manufacturer are all conventional products that can be purchased on the market.

[0028] The first embodiment of the present application provides a plant fiber composite EVA foamed material, and the raw materials include modified plant fiber and EVA with a mass ratio of (1:9) to (4:6).

[0029] The modified plant fiber is obtained by modifying the plant fiber after activating the zinc ricinoleate with methyl glycine diacetic acid trisodium (MGDA) and L-sodium lysine.

[0030] The present application activates the zinc ricinoleate by using the double chelation system constructed by methyl glycine diacetic acid trisodium (MGDA) and L-sodium lysine. After activation, a small particle or micelle rich in free ricinoleate and chelated zinc complex is formed. The hydrophobic long-chain alkyl part of the micelle tends to adsorb on the surface of the plant fiber or embed in the hydrophobic region (such as the amorphous region and the small fissure) of the microstructure of the plant fiber. The hydrophilic carboxylate or chelating group is oriented towards the aqueous phase or forms a hydrogen bond with the hydroxyl group of the plant fiber. Finally, a dense hydrophobic-hydrophilic transition layer (interface layer) is formed on the surface of the plant fiber, which greatly reduces the surface energy and affinity for water, significantly hydrophobizes and reduces the moisture absorption rate. The hydrophobic coating formed between the plant fiber and the hydrophobic EVA melt reduces the interfacial tension between the two phases and improves the compatibility, which is conducive to the dispersion of the fiber in the melt and the mechanical interlocking of the interface. In general, the hydrophobicity, dispersibility and compatibility of the plant fiber modified by the zinc ricinoleate activated by MGDA and L-sodium lysine are significantly improved. The foamed material prepared by blending the plant fiber with EVA has significantly improved cell uniformity.

[0031] The modified plant fibers are distributed in the EVA melt like a micro "support point", which anchors in the melt, inhibits the melt from thinning and breaking, and enhances the ability of the cell wall to resist tensile thinning when the foaming agent decomposes and the gas expands to open the cell wall. During the cell stabilization process, the modified plant fiber acts as a "skeleton" or "reinforcing rib" in the cell wall, preventing the cell from merging or breaking due to internal gas pressure or external stress during growth or before cooling and setting.

[0032] The L-lysine sodium used in the present application has a double amino group (one alpha-amino and one side chain epsilon-amino) and a flexible methylene chain, is a water-soluble salt type amino acid derivative with basic side chains and long chain structures, and can achieve the three effects of stable complexation of Zn²⁺, enhanced fiber binding and optimized arrangement of the hydrophobic layer. Specifically, when the zinc ricinoleate is activated, the basic side chain of L-lysine sodium makes the reaction environment alkaline, can form a stable five-membered ring or six-membered ring chelate with Zn²⁺, effectively captures the zinc ions in zinc ricinoleate, and promotes the dissociation of zinc ions; the long chain structure can anchor the fiber, and the water-soluble salt form can transfer ions, ultimately making the MGDA chelate free Zn²⁺ form [Zn(MGDA)]⁻ complex ions and stably bind with plant fibers; due to the molecular structure of L-lysine sodium, the hydrophilic end: sodium carboxylate (-COO⁻), amino (-NH3⁺), and the hydrophobic end: long alkyl chain (-(CH2)4-), this structure gives it surfactant properties, can form micelles in the aqueous phase, wrap the hydrophobic zinc ricinoleate fragments, improve the dispersion stability, and the long carbon chain side group forms a hydrophobic barrier around the chelate, preventing the re-aggregation of dissociated zinc ricinoleate particles.

[0033] In the process of implementing the present application, the applicant has conducted experiments on other water-soluble salt type amino acid derivatives with basic side chains and long chain structures, such as L-arginine sodium, L-histidine sodium, Nε-acetyl-L-lysine sodium, L-lysine ethyl ester hydrochloride, L-ornithine sodium, etc., but the experimental results show that the water contact angle of the modified plant fibers ultimately obtained based on these amino acid derivatives is less than 90°, showing hydrophilicity, and cannot effectively hydrophobically modify zinc ricinoleate. This is due to the differences in the number, position or adaptive structure of the functional groups of these amino acid derivatives. For example, the strong positive charge and steric hindrance of the guanidino group of L-arginine sodium interfere with complexation; the imidazole group of L-histidine sodium has weak coordination ability and a rigid structure that limits arrangement; acetylation of Nε-acetyl-L-lysine sodium causes the epsilon-amino group to be inactive; the amino group of L-lysine ethyl ester hydrochloride is protonated and loses coordination ability; L-ornithine sodium has few coordination sites and insufficient flexibility.

[0034] The amount of trisodium methyl glycine diacetate, sodium L-lysine and zinc ricinoleate is determined according to the synergistic mechanism and quantitative reaction requirements of MGDA, sodium L-lysine in the activation of zinc ricinoleate, such as the degree of dissociation of zinc ions, pH value, anchoring fiber capacity, etc. In some preferred embodiments, the mass ratio of trisodium methyl glycine diacetate, sodium L-lysine and zinc ricinoleate is 1: (1.8-3.5): (1.6-4.2).

[0035] For the amount of modified plant fiber and EVA, generally speaking, the amount of modified plant fiber is determined according to the performance requirements of the application scene of the foaming material. According to the prior art, the amount of modified plant fiber should not exceed 40% of the total mass of the composite material. If it exceeds 40%, the polymer continuity will be reduced, it will be difficult to effectively support the formed bubbles, and defects such as bubble hole rupture and bubble merging will occur, and the comprehensive performance of the foaming material will also be significantly reduced.

[0036] For plant fibers, because plant fibers themselves have hydrophilic groups and micropores, and can match the modification mechanism, common plant fibers are suitable for the present application, including seed or hair fibers, bast fibers, leaf vein fibers, fruit fibers, grass / poaceae fibers, etc. For example, bamboo fiber, ramie fiber, straw fiber, cotton fiber, kapok fiber, flax fiber, jute fiber, red hemp fiber, hemp fiber, sisal fiber, banana fiber, coconut shell fiber, sugarcane residue fiber, reed fiber, miscanthus fiber.

[0037] In some preferred embodiments, for different plant fibers, at least one pretreatment of washing, drying and swelling treatment can be selectively performed before modification. The washing is to remove impurities; the moisture content of the plant fiber after drying is generally less than 3%; the swelling treatment is to enhance the fiber porosity, generally by soaking the plant fiber in warm water at 40-60°C for 1-2 hours. In addition, plant fibers containing waxes or highly carbonized plant fibers can be pretreated by alkali boiling and acid etching to restore hydrophilicity. The corresponding pretreatment method is a common pretreatment means in the art, which does not need to be specially limited.

[0038] In some preferred embodiments, in order to control the cell size of the foaming material, the plant fiber is generally crushed to 600-1000 mesh for use.

[0039] For the method of modifying plant fibers, it specifically comprises: vacuum impregnating the plant fiber in the activated zinc ricinoleate solution until the chelation reaction is completed, and then drying.

[0040] In some preferred embodiments, if the effect of the plant fiber after the impregnation does not meet the expectation, such as plant fiber micro-fissure coating, zinc layer peeling, wet heat aging, etc., a secondary impregnation can be performed after drying, i.e. the plant fiber after completing the chelation reaction is again immersed in the activated zinc ricinoleate solution for 30-60 min, and then dried again. Through the secondary impregnation, the cross-linking effect can be enhanced, and the fissure coverage rate is > 95%; at the same time, the fiber brittleness can be avoided. During the secondary impregnation, the solid-liquid ratio can be adaptively selected according to the effect, such as 1:(3-8) g / g.

[0041] The above "micro-fissure coating" refers to that the viscosity of the activated zinc ricinoleate solution (containing MGDA / L-lysine sodium chelate) is significantly reduced (≈1200 cP), and the surface tension is reduced, and the micro-fissure (width is usually 1-50 μm) of the plant fiber is deeply penetrated by the capillary action. The "zinc layer peeling" is fundamentally caused by the failure to establish a firm chemical bond between the plant fiber and the zinc layer, and is triggered by external factors such as heat and humidity, mechanical stress, etc.

[0042] It should be noted that the determination method for completing the chelation reaction is that the solution changes from blue-green to dark green translucent, which proves that the Zn²⁺-MGDA chelate has combined with the hydroxyl group on the surface of the plant fiber at this time.

[0043] After completing the chelation reaction, the excess solution can be combined and then vacuum dried, for example, vacuum drying at 75℃ for 12 hours can be performed to avoid the oxidation and decomposition of zinc salt caused by high temperature, and the specific drying method, temperature and time can be adjusted by the person skilled in the art according to the actual needs.

[0044] The second embodiment of the present application provides a preparation method of plant fiber composite EVA foaming material, comprising:

[0045] After the modified plant fiber is mixed with EVA, it is mixed at 90-110℃ for 15-30 min, and then foamed at 180-190℃ and 8-15 Mpa for 8-15 min.

[0046] In some preferred embodiments, an additive is also added during the mixing process. Since the compression resistance of the EVA foaming material itself is poor, the tear strength is low, and the performance requirements are different for different application scenarios of the foaming material, the additive to be added will be adjusted accordingly, and the selection and use of the additive are common technical means for the person skilled in the art. For example, for products with high compression resistance, high tear strength and high resilience, different additives need to be used to achieve the required performance.

[0047] The preparation and performance of the plant fiber composite EVA foaming material are described in detail below through a plurality of specific embodiments.

[0048] The "parts" used below are all "weight parts".

[0049] Preparation of bamboo fiber composite EVA foaming material

[0050] Preparation of modified bamboo fiber: after washing and drying the bamboo fiber to a moisture content of less than 3%, soak in warm water at 40°C for 1 hour to complete the pretreatment; MGDA: L-lysine sodium: zinc ricinoleate is configured in the amount ratio of 1:2:2 to obtain an activated zinc ricinoleate solution; the pretreated bamboo fiber is vacuum impregnated in the activated zinc ricinoleate solution at a solid-liquid ratio of 1:20 g / g until the solution changes from blue-green to dark green translucent; after taking out the bamboo fiber, squeeze out the excess solution, vacuum dry at 75°C, then impregnate in the activated zinc ricinoleate solution again, impregnate at 45°C for 40 min, and dry to a moisture content of less than 3% after impregnation to obtain modified bamboo fiber powder.

[0051] Preparation of modified bamboo fiber foaming material: EVA 80 parts, 15 parts of 800 mesh modified bamboo fiber powder, EVA JQ9107 anti-shrinkage agent 5 parts, stearic acid 2 parts, zinc stearate 1 part, zinc oxide and azodicarbonamide blended powder 5 parts, 2,4-di-tert-butyl peroxide isopropylbenzene 0.5 parts, polybutyl methacrylate 0.5 parts, TAIC 0.2 parts; after mixing the above materials, mix at 100°C for 15 min, discharge, press into tablets, cool, then foam for 15 min at a temperature of 185°C and a pressure of 10 MPa.

[0052] In order to more intuitively show the hydrophilic and hydrophobic properties of the modified bamboo fiber, the modified bamboo fiber powder is pressed into tablets and then tested for hydrophilic and hydrophobic properties using a water contact angle tester (the same test method as the following comparative examples). The demonstration and test results of the hydrophilic and hydrophobic properties of the modified bamboo fiber in this example are shown in Figure 1 The test results show that the droplet forms a water bead on the surface of the modified fiber, with a contact angle of 131.8°, and the contact angle changes to 81° after ten minutes, indicating a significant improvement in hydrophobicity. The scanning electron microscope images and cross-sectional cell images of the foaming material prepared in this example are shown in Figure 3 Figure 4 It can be seen that, compared with Comparative Example 1-2, the foaming material prepared in this example has a more uniform cell structure and more excellent performance.

[0053] Preparation of bamboo fiber composite EVA foaming material

[0054] ​Preparation of modified ramie fiber: The pretreated 800 mesh ramie fiber was washed, dried to a water content of less than 3%, then soaked in warm water at 45°C for 1h, and the pretreatment was completed; MGDA: L-lysine sodium: zinc ricinoleate was configured according to the mass ratio of 1:3:2 to prepare the activation solution, and the activated zinc ricinoleate solution was obtained by mixing uniformly; the pretreated ramie fiber was vacuum impregnated in the activated zinc ricinoleate solution according to the solid-liquid ratio of 1:22g / g; the ramie fiber was taken out after squeezing out the excess solution, and vacuum dried at 75°C for 12 hours; the dried ramie fiber powder was again immersed in the activated zinc ricinoleate solution, and soaked at 45°C for 45min; after the soaking was completed, the ramie fiber powder was dried to a water content of less than 3%, and the modified ramie fiber powder was obtained for standby use.

[0055] Preparation of modified ramie fiber foamed material: EVA 75 parts, 20 parts of 800 mesh modified ramie fiber powder, EVA JQ9107 anti-shrinkage agent 5 parts, stearic acid 2 parts, zinc stearate 1 part, zinc oxide and azodicarbonamide blended powder 5 parts, 2,4-di-tert-butyl peroxide isopropyl benzene 0.5 parts, polybutyl methacrylate 0.5 parts, TAIC 0.2 parts; the above materials were mixed and mixed at 100°C for 15min, and then discharged, pressed into a sheet, cooled, foamed for 15min, the temperature was 185°C, and the pressure was 10MPa.

[0056] Example 3 Preparation of rice hull fiber composite EVA foamed material

[0057] Preparation of modified rice hull fiber: The pretreated 800 mesh rice hull fiber was washed, dried to a water content of less than 3%, then soaked in warm water at 45°C for 1h, and the pretreatment was completed; MGDA: L-lysine sodium: zinc ricinoleate was configured according to the mass ratio of 1:3:3 to prepare the activation solution, and the activated zinc ricinoleate solution was obtained by mixing uniformly; the pretreated rice hull fiber was vacuum impregnated in the activated zinc ricinoleate solution according to the solid-liquid ratio of 1:18g / g; the rice hull fiber was taken out after squeezing out the excess solution, and vacuum dried at 75°C for 12 hours; the dried rice hull fiber powder was again immersed in the activated zinc ricinoleate solution, and soaked at 50°C for 50min; after the soaking was completed, the rice hull fiber powder was dried to a water content of less than 3%, and the modified rice hull fiber powder was obtained for standby use.

[0058] Preparation of modified rice hull fiber foamed material: EVA 65 parts, 30 parts of 800 mesh modified rice hull fiber powder, EVA JQ9107 anti-shrinkage agent 5 parts, stearic acid 2 parts, zinc stearate 1 part, zinc oxide and azodicarbonamide blended powder 5 parts, 2,4-di-tert-butyl peroxide isopropyl benzene 0.5 parts, polybutyl methacrylate 0.5 parts, TAIC 0.2 parts; the above materials were mixed and mixed at 100°C for 15min, and then discharged, pressed into a sheet, cooled, foamed for 15min, the temperature was 185°C, and the pressure was 10MPa.

[0059] Example 4 Preparation of straw fiber composite EVA foaming material

[0060] Preparation of modified straw fiber: The pretreated 800 mesh straw fiber was washed, dried to a moisture content of less than 3%, then soaked in warm water at 45°C for 1 hour to complete the pretreatment; the activation solution was prepared by mixing MGDA, L-lysine sodium and zinc ricinoleate in a mass ratio of 1:3:4, and then uniformly mixed to obtain the activated zinc ricinoleate solution; the pretreated straw fiber was vacuum impregnated in the activated zinc ricinoleate solution at a solid-liquid ratio of 1:15 g / g; the ramie fiber was taken out and the excess solution was squeezed out, and then dried at 75°C for 12 hours; the dried straw fiber powder was again impregnated in the activated zinc ricinoleate solution, and soaked at 50°C for 50 minutes; after impregnation, the modified straw fiber powder was dried to a moisture content of less than 3% for standby use.

[0061] Preparation of modified straw fiber foaming material: EVA 55 parts, 35 parts of 800 mesh modified straw fiber powder, EVAJQ9107 anti-shrinkage agent 10 parts, stearic acid 2 parts, zinc stearate 1 part, zinc oxide and azodicarbonamide blended powder 5 parts, 2,4-di-tert-butyl peroxide isopropylbenzene 0.5 parts, polybutyl methacrylate 0.5 parts, TAIC 0.2 parts; the above materials were mixed and kneaded at 100°C for 15 minutes, then discharged, pressed into a sheet, cooled, foamed for 12 minutes at a temperature of 190°C and a pressure of 10 MPa.

[0062] Comparative Example 1

[0063] Compared with Example 1, the only difference is that the modification of pretreated bamboo fiber is cancelled, and the addition amount of bamboo fiber is consistent, and the rest of the preparation steps is consistent.

[0064] The hydrophilic and hydrophobic demonstration and test results of the unmodified bamboo fiber in this comparative example are shown in Figure 2 The test results show that the unmodified bamboo fiber has strong hydrophilicity due to the presence of hydrophilic groups such as hydroxyl (-OH) on the surface, and the water droplets on the surface are completely absorbed within 5 seconds, showing strong hydrophilicity. The scanning electron microscope images and cross-sectional cell images of the foaming material prepared in this comparative example are shown in Figure 3 a、 Figure 4 a.

[0065] Comparative Example 2

[0066] Compared with Example 1, the only difference is that the pretreated bamboo fiber is modified with 1% silane coupling agent silanol instead of the activated zinc ricinoleate modified pretreated bamboo fiber.

[0067] The plant fiber was placed in a high-speed stirring mixer at 80°C, and the corresponding amount of KH550 was added dropwise. The mixture was stirred for 1 h, and then the modified fiber was taken out and used. The amount of modified bamboo fiber was consistent with that in Example 1, and the remaining preparation steps were consistent.

[0068] The scanning electron microscope image and the cross-sectional cell image of the foamed material prepared in this comparative example are shown in Figure 3 b, Figure 4 b.

[0069] Comparative Example 3

[0070] Compared with Example 1, the only difference is that only an equal amount of MGDA is used to activate zinc ricinoleate, and the amount of modified bamboo fiber is consistent, and the remaining preparation steps are consistent.

[0071] The modified bamboo fiber prepared in this comparative example is almost not hydrophobic, and the liquid drop is quickly absorbed after contacting the modified bamboo fiber, and the contact angle cannot be stabilized at an accurate value. The contact angle value is 66° within a short time after dropping. The scanning electron microscope image of the cell of the foamed material prepared in this comparative example is shown in Figure 5 a.

[0072] Comparative Example 4

[0073] Compared with Example 1, the only difference is that only an equal amount of L-lysine sodium is used to activate zinc ricinoleate, and the amount of modified bamboo fiber is consistent, and the remaining preparation steps are consistent.

[0074] The modified bamboo fiber prepared in this comparative example is almost not hydrophobic, and the liquid drop is quickly absorbed after contacting the modified bamboo fiber, and the contact angle cannot be stabilized at an accurate value. The contact angle value is 65° within a short time after dropping. The scanning electron microscope image of the cell of the foamed material prepared in this comparative example is shown in Figure 5 b.

[0075] Comparative Example 5

[0076] Compared with Example 1, the only difference is that an equal amount of unactivated zinc ricinoleate is used to modify the pretreated bamboo fiber, and the amount of modified bamboo fiber is consistent, and the remaining preparation steps are consistent.

[0077] The modified bamboo fiber prepared in this comparative example is almost not hydrophobic, and the liquid drop is quickly absorbed after contacting the modified bamboo fiber, and the contact angle cannot be stabilized at an accurate value. The contact angle value is 63° within a short time after dropping. The scanning electron microscope image of the cell of the foamed material prepared in this comparative example is shown in Figure 5 c.

[0078] Comparative Example 6

[0079] The difference compared with Example 1 is only that the mass ratio of MGDA, sodium L-lysine and zinc ricinoleate is 1:1:2.

[0080] Comparative Example 7

[0081] The difference compared with Example 1 is only that the mass ratio of MGDA, sodium L-lysine and zinc ricinoleate is 1:4:2.

[0082] Comparative Example 8

[0083] The difference compared with Example 1 is only that the amount of modified bamboo fiber and EVA is 5 parts.

[0084] Comparative Example 9

[0085] The difference compared with Example 1 is only that the amount of modified bamboo fiber and EVA is 45 parts.

[0086] The effect detection detection method for the above examples and comparative examples is shown in Table 1, and the detection results are shown in Tables 2-3.

[0087] Table 1: Performance detection method

[0088]

[0089] Table 2: Detection results of Examples 1-4

[0090]

[0091] Table 3: Detection results of Comparative Examples 1-9

[0092] .

[0093] The above only describes the preferred embodiments of the present application and is not used to limit the present application. For those skilled in the art, the present application can have various modifications and changes. Any modification, equivalent replacement, improvement, etc. within the spirit and principles of the present application shall be included in the protection scope of the present application.

Claims

1. A plant fiber composite EVA foam material, characterized in that, The raw materials consist of modified plant fibers and EVA in a mass ratio of (1:9) to (4:6); The modified plant fiber is prepared by: preparing an activation solution by mixing trisodium methylglycine diacetate, sodium L-lysine and zinc ricinoleate in a mass ratio of 1:(1.8-3.5):(1.6-4.2), and obtaining an activated zinc ricinoleate solution; immersing the plant fiber in the activated zinc ricinoleate solution under vacuum until the chelation reaction is completed, and then drying it.

2. The plant fiber composite EVA foam material as described in claim 1, characterized in that, The plant fiber includes any one of seed or hair fiber, bast fiber, leaf vein fiber, fruit fiber, and grass / gramineous fiber.

3. The plant fiber composite EVA foam material as described in claim 2, characterized in that, The plant fiber includes any one of bamboo fiber, ramie fiber, straw fiber, cotton fiber, kapok fiber, flax fiber, jute fiber, kenaf fiber, hemp fiber, sisal fiber, abaca fiber, coconut shell fiber, sugarcane bagasse fiber, reed fiber, and miscanthus fiber.

4. The plant fiber composite EVA foam material as described in any one of claims 1, 2, and 3, characterized in that, Before modifying plant fibers, at least one of the following pretreatments is performed: washing, drying, and swelling.

5. The plant fiber composite EVA foam material as described in claim 1, characterized in that, The solid-liquid ratio of plant fiber to activated zinc ricinoleate solution was 1:(8-25)g / g.

6. The plant fiber composite EVA foam material as described in claim 1, characterized in that, After drying, the plant fibers that have completed the chelation reaction are immersed again in an activated zinc ricinoleate solution for 30-60 minutes and then dried again.

7. The method for preparing the plant fiber composite EVA foam material according to any one of claims 1-6, characterized in that, Include: After mixing the modified plant fiber with EVA, knead it at 90-110℃ for 15-30 minutes, and then foam it at 180-190℃ and 8-15 MPa for 8-15 minutes.

8. The method for preparing the plant fiber composite EVA foam material as described in claim 7, characterized in that, Additives were also added during the mixing process.

Citation Information

Patent Citations

  • Mixtures of (2e)-3-(1, 3-benzodioxol-5-yl)-n-phenyl-n-(tetrahydro-3-furanyl)-2-acrylamide and uses

    CN119486725A

  • Thermoformable dual network hydrogel compositions

    WO2017079248A1